Participación del receptor H4 de histamina en la transición epiterial-mesenquimática de células de carcinoma mamario humano MDA-MB-231 - Táquez Delgado, Mónica Alejandra (2017)
Metastases are the cause of 90% of human cancer deaths. The mesenchymal epithelial transition (EMT) is a process that contributes to invasion and metastasis. During EMT epithelial cells acquire a more elongated morphology, exhibit changes in adhesion, motility and ability to degrade the extracellular matrix, as well as resistance to apoptosis.\nWe previously demonstrated that histamine is able to differentially modulate migration and gelatinolytic activity in mammary tumor cells MDA-MB-231, stimulating at doses lower than 1 ?M and inhibiting at doses greater than 10 ?M. Preliminary results from our studies indicated that stimulation of histamine H4 receptor in MDA-MB-231 cells reproduces the effects observed with histamine at low doses whereas H2 receptor stimulation is associated with effects obtained with doses of histamine greater than 10 ?M.\nThe objective of this work was to go further into the study of the role of histamine H4 receptor in the TEM of the triple negative mammary carcinoma MDA-MB-231 human cell, evaluating morphological changes, molecular and functional markers and some components of potential signaling pathways involved as well as the activation of TGF-? type I receptor induced by H4 agonists.\nThe H4 agonists promoted cell scattering, increased the expression of the mesenchymal marker vimentin and increased nuclear localization or/and the expression of ?-catenin and Slug transcription factor. Significant improvements in MMP9 metalloproteinase activity, cell migration and invasion were also observed. We also demonstrated that phosphorylation of c-Src protein kinase was involved in cell migration among other characteristic events of TEM. Previous treatment of mammary tumor cells with the H4 antagonist JNJ7777120 blocked the effects produced by H4 agonists and helped to highlight the role of the H4 receptor in the induction of TEM-related events. Moreover, H4 agonists increased the expression of TGF-?1 in MDA-MB-231 cells whereas the use\nof the TGF-? type I receptor kinase inhibitor suggested a potential crosstalk between both receptors to promote TEM through a signaling involving Src phosphorylation.\nIn summary, the results of this work indicate that stimulation of histamine H4 receptors favors the expression of the invasive phenotype in MDA-MB-231 cells and the activation of TGF-? Type I receptor.\nBasal and triple-negative tumors are difficult to treat, biologically more aggressive, and of very poor prognosis. We believe that the identification of factors that initiate, modulate and execute EMT-related events could provide the basis for the development of more efficient strategies to fight against metastasis of epithelial cancers, providing targets for the improvement of therapies that address pharmacological modification of pathways and signaling elements.